(untitled) (Economic and Political Thought, 2016)
The main purpose of this article is to analyse the system of redistricting regarding the elections to the US House of Representatives and to examine what consequences it has for the entire political system. The article is based on a hypothesis that redistricting does not have a direct impact on elections results and on the political system. However, it has an important indirect impact, strengthening already existing trends, and also a mediating impact, consisting in the transmission of changes from one level of the political system to another level. The article consists of three parts. The first one is devoted to historical evolution of the redistricting system, from the creation of the United States till the 1960s. The second part discusses three subsequent phases of the evolution of the contemporary redistricting system. The third part investigates how redistricting affects the political system as a whole. The following issues are analysed in this part: direct impact on elections results, alleged decline in electoral competition, growing polarization of the political arena and the electorate, and representatives’ attentiveness to their constituents’ problems.